2022
DOI: 10.1038/s41392-022-00885-4
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal and spatial cellular and molecular pathological alterations with single-cell resolution in the adult spinal cord after injury

Abstract: Spinal cord injury (SCI) involves diverse injury responses in different cell types in a temporally and spatially specific manner. Here, using single-cell transcriptomic analyses combined with classic anatomical, behavioral, electrophysiological analyses, we report, with single-cell resolution, temporal molecular and cellular changes in crush-injured adult mouse spinal cord. Data revealed pathological changes of 12 different major cell types, three of which infiltrated into the spinal cord at distinct times pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 56 publications
6
77
1
1
Order By: Relevance
“…Here, we used the spatial mapping maps of known typical markers in different cell types to verify the spot division after applying the AddModule Score function from the Seurat R package. Fortunately, we found that each cluster was the most likely reasonable cell type shown in the previous studies [10,20,21].…”
Section: Treatment Strategies To Eliminate Scars Provided By St Techn...supporting
confidence: 57%
“…Here, we used the spatial mapping maps of known typical markers in different cell types to verify the spot division after applying the AddModule Score function from the Seurat R package. Fortunately, we found that each cluster was the most likely reasonable cell type shown in the previous studies [10,20,21].…”
Section: Treatment Strategies To Eliminate Scars Provided By St Techn...supporting
confidence: 57%
“…Interestingly, regional identity of astrocytes, as defined by gene expression signatures, is preserved even in a reactive state (Diaz-Castro et al, 2021). scRNA-seq confirmed that distinct astrocyte subtypes mount different transcriptional responses with temporal variation to the same CNS insult (Hasel et al, 2021;Li et al, 2022). Diseasespecific interaction of transcriptional regulators together with engagement of core reactivity-promoting transcription factors in reactive astrocytes collectively contributes to differential gene expressions that determine disease-specific astrocytic phenotype (Burda et al, 2022).…”
Section: Bioenergetic Supportmentioning
confidence: 89%
“…Evolution of astrocyte complexity was proposed to enable the integration and expansion of processing power of the human brain ( Oberheim et al, 2006 ). scRNA-seq revealed regional astrocyte diversity, defined transcriptomically, in the healthy brain and spinal cord of mice and humans ( Saunders et al, 2018 ; Hasel et al, 2021 ; Li et al, 2022 ; Sadick et al, 2022 ).…”
Section: Astrocyte Diversity: An Astrocyte Subtype That Promotes Axon...mentioning
confidence: 99%
“…Furthermore, with transcriptional analysis of individual cells in the crush-injured spinal cord in adult mice, other authors demonstrated novel microglia and astrocyte subtypes and their dynamic conversions into additional stage-specific subtypes/states. Most of the dynamic changes occurred 3 days after injury; a recovery trend was observed between 3 and 14 days after injury, and after 14 days, reactivation of microglia and a further decrease in neuronal, astrocytic, and endothelial populations along with a continued increase in leukocyte population were evident [ 40 ].…”
Section: Main Inflammatory Events In Scimentioning
confidence: 99%